Bucolic metaphors : history, subjectivity and gender in the early modern Spanish pastoral - Hernández-Pecoraro, Rosilie (North Carolina studies in the Romance languages and literatures, 2006)
"An in-depth examination of the cultural functions of the pastoral in Spain, this study of Montemayor's La Diana and Cervantes's pastoral texts moves away from studies that consider this literature as purely escapist and imitative. Rosilie Hernandez-Pecoraro considerably expands the discussion on the importance of the pastoral genre to early modern Spanish studies and supplements the ways in which these texts have conventionally been considered by Hispanists."--Provided by publisher